2019
DOI: 10.1177/0892705719882074
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on adhesion, flexibility, interlaminar shear strength, and damage mechanism of jute/rubber-based flexible “green” composite

Abstract: Determining the interlaminar shear strength (ILSS) of the composite laminates is vital for deciding their usage in any engineering applications. The matrix used and its curing characteristics are vital in deciding the ILSS of the composite. Present work deals with an experimental study on adhesive behavior, degree of flexibility, ILSS, and damage mechanism of the novel jute/rubber-based flexible “green” composite. The proposed flexible composites were prepared in three different stacking sequences, namely jute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 43 publications
0
20
0
1
Order By: Relevance
“…13 Also, it was found that by using flexible matrix materials, the catastrophic failure of the components can be eliminated. [14][15][16][17] Various researchers have reported the abrasive wear studies of different types of composites. 18,19,[20][21][22][23][24][25][26][27][28] Carbon reinforced polymer matrix composites was subjected to wear and its behaviour was studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Also, it was found that by using flexible matrix materials, the catastrophic failure of the components can be eliminated. [14][15][16][17] Various researchers have reported the abrasive wear studies of different types of composites. 18,19,[20][21][22][23][24][25][26][27][28] Carbon reinforced polymer matrix composites was subjected to wear and its behaviour was studied.…”
Section: Introductionmentioning
confidence: 99%
“…13 Also, it was found that by using flexible matrix materials, the catastrophic failure of the components can be eliminated. 1417…”
Section: Introductionmentioning
confidence: 99%
“…Jute is a lignocellulose fibre having promising mechanical and thermal properties. Its light-weight, less cost and ease of availability made it ideal to use it as reinforcement, using these type of natural fib re material as reinforcement is eco-friendly way of dealing the natural fibre [26][27][28], whereas SiC are ceramic particles used in order to increase the hardness of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…12 Here, it was to be emphasized that the existence of high compatibility and good adhesion between components led the formed composites to exhibit better mechanical performance compared to both partly miscible and immiscible polymer matrices. 13,14 In other words, the formation of relatively stronger and effective intermolecular attraction forces (Van der Waals forces) between the component polymer chains in the matrix provides both the additional endurance and relatively larger withstanding capability against the deformation to the polymeric materials, 15 which results in the reinforcement of the polymer composites. Furthermore, the various chemical methods like silane and alkaline treatments, acetylation, and bleaching were also used in order to get rid of this compatibility problem coming out in the polymer matrices.…”
Section: Introductionmentioning
confidence: 99%